1983
DOI: 10.1128/iai.42.2.842-844.1983
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a semisynthetic vaccine to Streptococcus pneumoniae type 3

Abstract: A semisynthetic vaccine to Streptococcus pneumoniae type 3 has been developed. The hexasaccharide [3)GlcpA,(l4)Glcp(1]3 was isolated from a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The results fit well to previous studies [14,15], wherein it was shown that a hexasaccharide derived from polysaccharide type 3 coupled without spacer as a pentasaccharide to KLH was capable of inducing protective immunity against type 3 pneumococci in mice.…”
Section: Streptococcus Pneumoniae Neisseria Meningitidis Haemophilus supporting
confidence: 91%
“…The results fit well to previous studies [14,15], wherein it was shown that a hexasaccharide derived from polysaccharide type 3 coupled without spacer as a pentasaccharide to KLH was capable of inducing protective immunity against type 3 pneumococci in mice.…”
Section: Streptococcus Pneumoniae Neisseria Meningitidis Haemophilus supporting
confidence: 91%
“…In the present study, NGL were constructed to promote both immunogenicity and antigenicity of these oligomannosides. Such an approach has been previously developed to produce antibodies against oligosaccharides from bacterial cell walls (28) or oligosaccharides isolated from different, human glycoproteins (29,32,36). However, the present use of 4-hexadecylaniline offers several advantages, since the binding of oligosaccharides to lipids is realized in a short time with a one-step procedure; the alkylaniline derivatives may also be easily detected by UV light.…”
Section: Discussionmentioning
confidence: 99%
“…In view of these problems, we attempted to develop a convenient model to determine the molecular basis of oligomannosidic recognition by experimental animal and human immune systems. Oligosaccharides were coupled to a lipid to form neoglycolipids (NGL) by a previously described method to study the antigenicity of oligosaccharides derived from human or bacterial glycoproteins (18,28,29,32,36). This work concerns oligosaccharides released from C. albicans PPM by mild acid hydrolysis (1,(24)(25)(26)33).…”
mentioning
confidence: 99%
“…Promising results have also been obtained following immunization with liposome-associated antigens; the oral (3,19,35,37,47) and parenteral (4,8,13,24,25,38,39,42) routes have been used for antigens of parasites (4,24,25,37,39), viruses (13,32), and bacteria (3,8,19,35,38,42,47). Their potential as adjuvants has been demonstrated in several studies, in which the use of liposome-associated antigens resulted in protective immunity (4,8,19,24,25,37,39,42) or at least cell-mediated (8) and humoral responses (3,13,38). The adjuvanticity of liposomes seems to depend on several factors including vesicle size and structure, lipid constitution, surface charge, antigen localization, the animal species immunized, route of immunization, and the distribution and number of lamellae.…”
mentioning
confidence: 99%